Implementation of TQM Based on ESQ in Assalaam Modern Islamic Boarding School Temanggung - Iqbal, Nur Muhammad; Usman, Nurodin (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2024)
This research is based on the quality of Islamic education that needs to be improved. This study aims to analyze the implementation of TQM and ESQ in Assalaam Modern Islamic Boarding School Temanggung. This research is a qualitative descriptive research. Data collection was carried out using observation, interviews, and documentation techniques. The results showed that: (1) Overall, Assalaam Modern Islamic Boarding School has implemented the TQM strategy well, with the principle of four things, namely customer satisfaction, respect for everyone, fact-based management, and continuous improvement. (2) ESQ at Assalaam Modern Islamic Boarding School is implemented by conducting trainings that focus on developing the personality and character of students, such as speech exercises and discussions. In addition, it is also taught always to implement three principles, namely the Pillars of Faith, the Pillars of Islam, and Ihsan (3). The students are taught how to convey religious messages clearly and easily understood by the community. However, not many students can become preachers in the community, and there still needs to be an improvement in the quality of learning and evaluation every year, especially in raising awareness and motivation for every student about the importance of being a preacher. This research recommends implementing ESQ-based TQM to improve the quality of learning in Islamic boarding schools in Indonesia.